Post-ERCP bacteremia caused by Alcaligenes xylosoxidans in a patient with pancreas cancer - Akcay Korhan; Caylan Rahmet; Koksal Iftihar; Aydin Kemalettin; Yilmaz Gurdal; Arslan Mehmet (BMC, 2006)
Abstract Alcaligenes xylosoxidans is an aerobic, motile, oxidase and catalase positive, nonfermentative Gram negative bacillus. This bacterium has been isolated from intestine of humans and from various hospital or environmental water sources. A.xylosoxidans is both waterborne and results from the poor-hygienic conditions healthcare workers are in. In this case report, the bacteremia which appeared in a patient with pancreas cancer after ERCP was described.